The potential Two Types of Green Macroalgae (Caulerpa racemosa and Caulerpa lentillifera) as a Natural Food Preservative from Jepara beach, Indonesia - Santosa, Gunawan Widi; Djunaedi, Ali; Susanto, AB; Pringgenies, Delianis; Ariyanto, Dafit; Pranoton, Aris Kabul (Trends in Sciences, 2024)
Green macroalgae, known locally as Latoh, is one of the green seaweeds consumed by the local community in Jepara and is beneficial for health. This study explores the potential of secondary metabolites from seaweed and its symbiotic bacteria as natural food preservatives and antibacterials. Seaweed samples were collected from the seagrass ecosystem of Panjang Island, Jepara, Indonesia. Subsequently, the samples were subjected to scanning electron microscopy analysis, proximate analysis, phytochemical analysis, thin layer chromatography, and high-performance liquid chromatography for amino acid analysis. A sample was subjected to a multistage extraction process using n-hexane, ethyl acetate, and methanol (1:5 w/v), each for 24 h. Symbiotic bacteria from seaweed were isolated, and enzymatic (proteolytic, amylolytic, and cellulolytic) and antibacterial testing against pathogenic bacteria Staphylococcus aureus and Escherichia coli was conducted using the disc diffusion method. The selected bacteria were subjected to molecular identification. The research showed that Caulerpa lentillifera had an ash content of 3.24 %, protein content of 0.57 %, and fat content of 0.337 %. Phytochemical analysis shows that the sample contains flavonoids, steroids, and alkaloids. HPLC analysis reveals that Caulerpa lentillifera has the highest content of aspartic acid (relative area: 11.90 %), glutamic acid (relative area: 13.43 %), and alanine (relative area: 9.03 %). Caulerpa racemosa sample shows the highest detector response for glutamic acid (relative area: 12.19%), aspartic acid (relative area: 11.10 %), and alanine (relative area: 9.63 %). The results indicate that 14 bacterial isolates were successfully isolated, with 6 isolates from Caulerpa lentillifera and 8 isolates from Caulerpa racemosa, all exhibiting enzymatic and antibacterial abilities. The research results concluded that the Latoh seaweed species Caulerpa lentillifera and Caulerpa racemosa and their symbiotic bacteria have the potential to be used as food preservatives. HIGHLIGHTS HPLC analysis showed that Caulerpa lentillifera had the highest content of aspartic acid, glutamic acid, and alanine. Caulerpa racemosa also had high levels of glutamic acid, aspartic acid, and alanine The research successfully isolated 14 bacterial isolates, with 6 isolates from Caulerpa lentillifera and eight isolates from Caulerpa racemosa, all exhibiting enzymatic and antibacterial abilities Molecular identification revealed the presence of identified bacteria such as Pseudoalteromonas arabiensis, Pseudoalteromonas piscicida, Pseudoalteromonas shioyasakiensis, and Vibrio alginolyticus seaweed species Caulerpa lentillifera and Caulerpa racemosa, along with their symbiotic bacteria, have the potential to be used as natural food preservatives due to their antibacterial and enzymatic pro perties GRAPHICAL ABSTRACT